An Empirical Analysis of the Impact of Non-oil Exports on the Economic Development of Nigeria - Stephen Ekeke; UTAI UPRASEN (무역연구, 16(5), 2020)
Purpose The purpose of this study is to analyze, examine and estimate the impact of Nigeria’s non-oil exports on its economic growth and development. Design/Methodology/Approach This study analyzed annual data gotten over the time-series period of 1981 to 2017. The study adopted the Auto-regressive Distributed Lag (ARDL) model. Findings The empirical results indicate that a statistically significant long run and positive relationship between non-oil exports and economic growth in Nigeria exists. The results indicated that a 1 percent increase in non-oil exports increases GDP growth by 0.48 percent at 1 percent significant level. The Toda-Yamamoto Granger Causality test also confirms a unidirectional causal relationship indicating that non-oil export causes an increase in the economic growth of Nigeria. Research Implications Previous studies on the non-oil exports of Nigeria did not factor the relative importance of foreign direct investment (FDI) and government expenditure (GXP) as necessary economic variables that influence growth in the economy. Their results do not adequately portray the magnitude of the impact of non-oil exports due to omitted variable bias. This study improves this point by adding these variables into the estimating equation and thereby reduce the omitted variable bias. Furthermore, this study seeks to contribute to the already existing literature and studies by examining Nigeria’s non-oil exports impact on economic growth in both the short run and long run using the ARDL model. KCI Citation Count: 1